2006
DOI: 10.1213/01.ane.0000218421.18723.cf
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anesthesia Using Single Injection Small-Dose Bupivacaine Versus Continuous Catheter Injection Techniques for Surgical Repair of Hip Fracture in Elderly Patients

Abstract: Aging and disease may make elderly patients particularly susceptible to hypotension during spinal anesthesia. We compared the hemodynamic effect of continuous spinal anesthesia (CSA) and small dose single injection spinal anesthesia (SA) regarding the incidence of hypotension. Seventy-four patients aged >75 yr undergoing surgical repair of hip fracture were randomized into 2 groups of 37 patients each. Group CSA received a continuous spinal anesthetic with a titration of 2.5 mg boluses every 15 min of isobaric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 20 publications
5
55
1
3
Order By: Relevance
“…Surveying the literature, both magnitude and frequency of hypotensive episodes are statistically significantly increased in patients with regional anaesthesia (evidence level II-III) [2,41,44,45,49,61] as well as the use of vasopressors (42.6% regional versus 14.3% general, P=0.001, evidence level II) [41]. Minville et al [63] showed less hypotension during continuous spinal anaesthesia and Juelsgaard et al [57], found evidence that hypotension is lowest only in patients receiving incremental doses of local anaesthetics, but observed no difference in the incidence of hypotension between anaesthetic techniques following single doses (evidence level II-III) [57,63]. Others reported no differences regarding hypotension comparing general and regional anaesthesia (evidence level II-III) [7, 25, 27, 29-31, 57, 65].…”
Section: Hypotensionmentioning
confidence: 99%
“…Surveying the literature, both magnitude and frequency of hypotensive episodes are statistically significantly increased in patients with regional anaesthesia (evidence level II-III) [2,41,44,45,49,61] as well as the use of vasopressors (42.6% regional versus 14.3% general, P=0.001, evidence level II) [41]. Minville et al [63] showed less hypotension during continuous spinal anaesthesia and Juelsgaard et al [57], found evidence that hypotension is lowest only in patients receiving incremental doses of local anaesthetics, but observed no difference in the incidence of hypotension between anaesthetic techniques following single doses (evidence level II-III) [57,63]. Others reported no differences regarding hypotension comparing general and regional anaesthesia (evidence level II-III) [7, 25, 27, 29-31, 57, 65].…”
Section: Hypotensionmentioning
confidence: 99%
“…Bulgular: Sol ventrikül ejeksiyon fraksiyonu SA ile değişmez iken, global boylamsal reconnoitering'de bir artış gözlendi (Δ−0,2±0,3% s We thought that this echocardiographic tool could bring a new perspective on the still controversial 'cardiac effect theory' of spinal anaesthesia (SA) (2)(3)(4)(5). Arterial hypotension is frequently observed during SA, especially in the elderly (6). This side effect, mainly due to preload and afterload decrease secondary to the sympathetic block, could cause a cardiac component per se (7).…”
Section: Resultsmentioning
confidence: 99%
“…Hypotension is frequently observed after SA, especially in the elderly (6). This side effect is an independent risk factor of mortality because of regional hypoperfusion (8).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Cependant, l'anesthésie locorégionale, réalisée sous forme de rachianesthésie, présente certains avantages sur l'anesthésie générale. 7 Des données issues de la littérature montrent qu'une diminution de la dose d'anesthésique local injectée en intrathécal en injection unique 8-10 ou continue 11,12 permet un retentissement hémodynamique moindre.…”
Section: Discussionunclassified